Analisis Determinan Pengaruh Kecenderungan Fraud Dalam Penyaluran Dana Bantuan Sosial Covid-19 Di Kota Pekalongan - Vicky Herviana; Arum Ardianingsih; Rika Adriyana (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
This study aims to analyze the determinants of the influence of the tendency of fraud in the distribution of social assistance funds in the city of Pekalongan. The distribution of social assistance funds provided by the Government to communities affected by COVID-10 needs special attention because in practice in the field there are many cases of fraud. This study uses a quantitative approach. The sample in this study were 32 employees at the Social Service of Pekalongan City. The type of data is primary data, namely questionnaires distributed to respondents. The results showed that the suitability of compensation, apparatus competence, and morality were not significant to the tendency of fraud. Internal control and organizational culture have a negative effect on the tendency of fraud, while the enforcement of regulations has a positive effect on the tendency of fraud.